Characteristics of University Budgeting Systems and Perceived Uncertainty Enviromental - Pasoloran, Oktavianus; Matasik, Ade Lisa (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This study aims to find empirical evidence of the direct influence of each budgeting characteristic, namely participation, clarity of targets, difficulty of targets, and budget feedback on managerial performance. In addition, this study wants to test the suitability of the perceived environmental uncertainty factor with the characteristics of budgeting targets. The respondents of this study were all structural officials within UKI Toraja totaling 110 people. This study uses two models to test each hypothesis developed in this study, namely regression analysis (stepwise), which is used to test hypotheses 1 to 4 and multiple regression methods with residual forms (residual approach) to test hypotheses 5 to 8. significant. The results showed that there was no significant influence of budget preparation participation and clarity of budget targets on managerial performance. However, this study shows that the lack of fit between characteristics and environmental uncertainty has an insignificant relationship. In other words, there is no expected inconsistency related to poor managerial performance. The ambiguity of these results may be caused by factors that have not been considered and controlled in relation to the use of residual analysis.